The Comparison Between Risk Factors of Invasive Candidiasis and 1,3-β-D-Glucan in Septic Pneumonia - Dwi Rosa Eka Agustina; Ungky Agus Setyawan; Teguh Rahayu Sartono (Jurnal Respirologi Indonesia, 2020)
Background: Invasive candidiasis (IC) occurs in immunocompromised and immunocompetent patients. It represents the 4th bloodstream infection in the ICU. Selection of patient characteristics based on risk factors in the 1,3-β-D-Glucan (BDG) examination provided a learning value in IC screening. The aim of this study was to assess the comparison of risk factors for IC and BDG levels using a cut off value of ≥80 pg/dl. Method: this cross-sectional study was conducted in 40 patients with septic pneumonia in ICU who had the risk factors of IC (multifocal colonization, broad-spectrum antibiotics, long term use of corticosteroids, and lymphocyte status) at Saiful Anwar Malang General Hospital. Results: There were 40 patients with risk factors of IC had positive BDG, but only 1 patient (2,5%) had candidemia and 14 patients (35%) had Candida sp from sputum culture. Comparison of BDG levels between group which used broad-spectrum antibiotics and those that did not wassignificant (P=0.020). Rank Spearman linear regression of the lymphocyte